Benefits of sexual practice during pregnancy: myth or reality? Comparative study and outcome of childbirth in Douala (Cameroon) - Essome, Henri; Egbe, Thomas O.; Nana, Théophile N.; Mve, Valère K.; Boten, Merlin; Tocki, Grâce T.; Halle, Gregory E. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Pregnancy is the term used to describe the period in which a foetus develops in the uterus and lasts 40 weeks measured from the last menstrual period. Anatomic and physiologic changes in pregnant women usually make couples to change their emotional and sexual activities that may impact childbirth. There are few studies in our setting that describe the roles of sexual practice during pregnancy and maternal-foetal outcomes of childbirth. Objective of this study aimed at assessing the benefits of sexual practice during pregnancy in a target population and to assess the outcome. Methods: We carried out a comparative cross-sectional study from February 2018 to May 2018, at the maternity of Laquintinie Hospital in Douala. Socio-demographic, obstetric, sexual history in pregnancy, birth and neonatal data were collected using a structured questionnaire. Univariate and multivariate analyses were conducted at a 95% confidence interval. Results: A total of 300 respondents completed study and 69.6% were favourable to sexual intercourse during pregnancy. Induction or augmentation of labour was common in the unfavourable group [OR: 2.52 (1.53-4.15); p=0.004]. Almost one in two participants gave birth by caesarean section and the indications for caesarean section were similar in both groups. Participants without sexual intercourse in pregnancy had a 9-fold increased risk of perineal tears [OR: 8.99 (4.02-10.1); p=0.001] and 5.4-fold risk of cervical tears [OR: 5.44 (2.44-8.73); p=0.0001]. Conclusions: Sexual practice in pregnancy appears to be protective against excessive use of oxytocin, perineal and cervical tears.